2017
DOI: 10.5551/jat.39065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 24-Week Aerobic and Resistance Training on Carotid Artery Intima-Media Thickness and Flow Velocity in Elderly Women with Sarcopenic Obesity

Abstract: Aim: Sarcopenic obesity (SO) is closely associated with cardiovascular disease (CVD) in elderly women. Increases in body fat and decreases in muscle mass are closely associated with increased carotid intima-media thickness (CIMT). The aim of this study was to examine the influence of a 24-week aerobic and resistance training program on carotid parameters in SO.Methods: Fifty elderly women (74.1 ± 6.1 years) with SO were randomly divided into an exercise group and a control group. The exercise group performed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(116 citation statements)
references
References 44 publications
4
96
0
Order By: Relevance
“…27 In another study in older women with obesity and sarcopenia in Korea, a 24-week aerobic and resistance training program effectively decreased carotid intima-media thickness and increased carotid flow velocity and wall shear ratio. 28 The findings from our study support a screening program for sarcopenia in older hospitalised patients using grip strength and lean mass calculated by anthropometric equation. In fact, other studies also found that it was feasible to measure grip strength than other indicators of sarcopenia such as gait speed.…”
Section: Discussionsupporting
confidence: 78%
“…27 In another study in older women with obesity and sarcopenia in Korea, a 24-week aerobic and resistance training program effectively decreased carotid intima-media thickness and increased carotid flow velocity and wall shear ratio. 28 The findings from our study support a screening program for sarcopenia in older hospitalised patients using grip strength and lean mass calculated by anthropometric equation. In fact, other studies also found that it was feasible to measure grip strength than other indicators of sarcopenia such as gait speed.…”
Section: Discussionsupporting
confidence: 78%
“…nificantly higher high-sensitivity CRP levels at admission in the low-ASMI group than in the high-ASMI group. Third, some studies have indicated an association between the loss of skeletal muscle mass and atherosclerosis [29][30][31] . Ochi et al indicated the negative relation between thigh muscle mass and brachial-ankle pulse wave velocity and carotid intima-media thickness in men, hypothesizing that common underlying factors may exist, such as increasing age, loss of physical activity, and malnutrition, in the two conditions, which can affect each other 32) .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, lack of physical activity might represent a contributing factor towards observed skeletal muscle mass reduction. To decrease the risk of muscle mass loss, power exercise in combination with aerobic exercise is recommended in some studies [12][13][14]. Whether this logical assumption translates into clinical practice remains unclear, so further studies are needed with proper design.…”
Section: Discussionmentioning
confidence: 99%
“…Dual-energy X-ray absorptiometry (DEXA) offers the best reproducibility and accuracy to detect such changes [9,10]. Some authors advocate the need for preventive programmes to overcome the problem of sarcopenia [11], such as the combination of aerobic and power exercises, which appears to be the most effective approach [12][13][14].…”
Section: Introductionmentioning
confidence: 99%